TEACHING WRITING THROUGH MICROSOFT WORD IN IMPROVING STUDENTS' WRITING SKILLS : An Experimental Study at a Madrasah Tsanawiyah in Garut - Gunawan, Agung (2009)
The title of this research is "Teaching Writing through Microsoft Word in Improving Students' Writing Skills" (An Experimental Study at a Madrasah in Garut). The purpose of this research is to find out whether or not the use of Microsoft Word in teaching writing helps the second grade students of Junior High School to improve their writing skills. Population of this research was the second grade students of a Madrasah in Garut and two classes were selected as sample. One class becomes the experimental class and another class becomes the control class. Each class consists of 30 students. This research was conducted based on Quasi-Experimental Design with pre-test and post-test for both experimental and control classes. The first writing performance (pre-test) was administered at the beginning of this research in order to find out students' initial ability in writing. Meanwhile, the second writing performance (post-test) was administered at the end of the research after treatments in order to find differences between students' score of experimental and control classes. The gained data shows that in first writing performance test, the mean of students' score ( ) does not show significant differences. The mean of students' score of experimental class is 59.83, while the mean of students' score of control class is 59.67. The result of test indicates that the value of is lower than the with the level of significant (α) at 0.05. Since the value is lower than the , the null hypothesis ( ) is accepted. It means that there is no difference on students' initial ability between experimental and control classes. Meanwhile, the gained data shows that in second writing performance test, the mean of students' score ( ) shows quite significant differences. The mean of students' score of experimental class is 67.80, while the mean of students' score of control class is 61.60. The result of test indicates that the value of is higher than the with the level of significant (α) at 0.05. Since the value is higher than the , the null hypothesis ( ) is rejected. It means that there is a significant difference on students' initial ability between experimental and control classes This result indicates that after the treatments, students' score of experimental class is higher than the students' score of control class who did not receive the treatments. It proves that using Microsoft Word in teaching writing improves students' writing skills.